Analisis Intensitas Kebisingan di Stasiun Kereta Api Tabing Kota Padang - Putra, Rian Pramana; Chandra, Deded (TSAQOFAH, 2025)
This study examines the intensity of traffic noise at Tabing Station in Padang City and the mapping of its distribution pattern on holidays and weekdays. Increased transportation activities in the station area have the potential to cause noise disturbances that can affect the comfort and health of the surrounding community. Measurements were made using a quantitative descriptive method using a Sound Level Meter. The study population was Tabing Station in Padang City with samples including the station road intersection, buildings along the measurement point, and the road shoulder. The results showed that the highest noise intensity occurred in the afternoon with an average of 83.78 dB on holidays during the arrival of the economy class Sibinuang Ekspress train on the Padang-Pariaman route, while the lowest value occurred in the morning with an average of 69.70 dB on holidays. Mapping the distribution of noise intensity was done using Inverse Distance Weighting (IDW) interpolation spatial analysis. The highest number of vehicles was found on Sunday (holiday) with a total of 6,794 units (motorcycles 4,187 units, cars 2,483 units, and fuso 124 units), while the lowest number of vehicles was found during the day on weekdays with a total of 2,246 units (motorcycles 1,590 units, cars 615 units, fuso 41 units).